Embodiment of Refugee and Migration Issues in Sculpture, Installation Art, and Metal Formation Arts in the Arab and Western Worlds (Al-Academy, 2026)
This study seeks to explore how sculpture and installation art, utilizing metal as a primary medium, can serve as effective artistic tools for embodying human emotions—particularly within sensitive humanitarian contexts such as migration and displacement. The research problem stems from the challenges artists face when attempting to express profound emotional and humanistic issues through unconventional materials like metal. These challenges are further intensified when striving to visually convey such emotions in a way that deeply resonates with the viewer.The study focuses on analyzing artworks that employ birds as both symbolic and emotional motifs, reflecting feelings of alienation, separation, and the pursuit of freedom. These representations act as visual metaphors for the emotional experiences associated with migration and displacement. Adopting a descriptive and analytical methodology, the study examines a selection of contemporary artworks to understand the aesthetic and conceptual techniques involved in metal sculpting, and how the underlying philosophies of these works are translated into compelling visual expressions.The significance of this research lies in its aim to establish the role of sculpture and installation art in addressing contemporary humanitarian issues, while enhancing the visual artist’s awareness of how the integration of materials and artistic disciplines can lead to a contemporary artistic vision rooted in authenticity and expressive depth. The study also seeks to present a contemporary artistic model that merges metalwork with spatial installation to communicate profound emotional experiences that engage the viewer on both emotional and intellectual levels